2009
DOI: 10.1007/s10470-009-9327-5
|View full text |Cite
|
Sign up to set email alerts
|

Design and characterization of the negative differential resistance circuits using the CMOS and BiCMOS process

Abstract: We investigate four novel negative-differentialresistance (NDR) circuits using the combination of the standard Si-based n-channel metal-oxide-semiconductor field-effect-transistor (NMOS) and SiGe-based heterojunction bipolar transistor (HBT). By suitably designing the parameters, we can obtain the K-or N-type currentvoltage (I-V) curve. Especially, the peak current of the combined I-V curve could be easy adjusted by the external voltage. In application, we utilize the NDR circuit to design an inverter circuit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 17 publications
(15 reference statements)
0
9
0
Order By: Relevance
“…III‐nitrides have also proven applications in tunnel diodes to achieve better negative differential resistance (NDR) effect and high peak to valley current ratio (PVCR) . The NDR effect has found wide applications in rectifiers, oscillator, frequency multiplier, memory, and fast switching devices . Among all III‐nitrides, outshining bulk gallium nitride (GaN) is a very promising material in various high voltage and RF applications .…”
Section: Introductionmentioning
confidence: 99%
“…III‐nitrides have also proven applications in tunnel diodes to achieve better negative differential resistance (NDR) effect and high peak to valley current ratio (PVCR) . The NDR effect has found wide applications in rectifiers, oscillator, frequency multiplier, memory, and fast switching devices . Among all III‐nitrides, outshining bulk gallium nitride (GaN) is a very promising material in various high voltage and RF applications .…”
Section: Introductionmentioning
confidence: 99%
“…The physical origin of NDR in biomolecules is still in debate and many mechanisms were proposed to explain this effect, such as polaron formation, resonance tunneling, conformational changes in the measured molecule, and the presence of molecular redox states [98]. NDR has attracted great interest in the last years, since it includes the existence of bistable states with an on/off ratio, on which many applications can be based, for instance memories, voltage--controlled oscillator, flip--flop and logic circuits [99]. Recently, Mentovich et al [98] verified direct correlation between NDR and redox centers, by comparing transistor effect in case of azurin or apo--azurin deprived from its redox center.…”
Section: Proteins For Bioelectronicsmentioning
confidence: 99%
“…The BJT uses the standard npn2 cell based on the CMOS process provided by the TSMC foundry. The operation of this NDR circuit had been discussed [5]. The Vgg value must be large enough to turn on both the MN1 and BJT devices.…”
Section: Ndr Circuit and Mobile Operationmentioning
confidence: 99%
“…Recently, our research group demonstrated a novel NDR circuit composed of the Si-based metal-oxide-semiconductor field effect transistors (MOS) and bipolar junction transistors (BJT), which was named as the MOS-BJT-NDR [5]. The great advantage of this NDR circuit is that we can fabricate their applications using the standard CMOS process.…”
Section: Introductionmentioning
confidence: 99%